Reactive microencapsulation of carbon allotropes in polyamide shell-core structures and their transformation in hybrid composites with tailored electrical properties - F. Oliveira; N. Dencheva; P. Martins; S. Lanceros-Mendez; Z. Denchev (eXPRESS Polymer Letters)
Polyamide 6 microcapsules (PAMC) loaded with 2–10 wt% of different carbon allotropes: carbon black, multiwalled carbon nanotubes, carbon nanofibers and graphite were synthesized via activated anionic polymerization (AAROP) of ε-caprolactam in solution performed in the presence of the respective micro- or nanosized loads. The forming high-molecular weight microporous PAMC showed typical diameters of 15–35 µm, the filler particles being entrapped in the core as proven by microscopy methods. The melt processing of the loaded microcapsules produced PA6/C-filler hybrid thermoplastic composites with homogeneous distribution of one or two C-fillers even at loads of up to 10% without any functionalization. The crystalline structure of all PAMC and molded composites was studied by thermal and X-ray diffraction methods focusing on possible structure modification during the transition from PAMC to molded plates. Mechanical tests in tension and electrical conductivity measurements showed that transforming loaded PAMC into composites by melt processing could be a facile and rapid method to fabricate polyamide composites with improved mechanical performance and tailored electrical and dielectric properties.